Economic Contributions of the Forest Industry and Forest-based Recreation in Florida in 2016 - Christa Dean Court; Alan W Hodges; Mohammad Rahmani (EDIS)
The state of Florida is half woods, with 26,807 square miles of forestland. Our extensive natural and planted pine and hardwood forests are used for production of a wide variety of wood building materials, consumer paper and packaging products, chemicals, and renewable biomass fuels. In addition to industrial forest-related activity, public forestlands in Florida support a variety of recreational activities, attract a significant number of recreational visitors, and provide many non-marketed environmental or ecosystem services. This 4-page fact sheet written by Christa Dean Court, Alan W Hodges, and Mohammad Rahmani and published by the UF/IFAS Food and Resource Economics Department describes a study that analyzed the economic contributions of the forest industry and forest-based recreation activities to the state of Florida in 2016. http://edis.ifas.ufl.edu/fe1051